2019
DOI: 10.21608/ijma.2019.17143.1030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vitamin D3 level in sino-nasal polypi

Abstract: Background: Vitamin D is a group of fat-soluble corticosteroid responsible for increasing intestinal absorption of calcium, magnesium, and phosphate, and multiple other biological effects. In humans, the most important compounds in this group are vitamin D3 [also known as cholecalciferol] and vitamin D2 [ergocalciferol].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The purpose of this review is to highlight the effect of VD levels on the pathogenesis and clinical manifestations of CRSwNP/sNP and clarify any therapeutic value of this hormone, in addition to current therapies for CRS. For this review, we managed to collect 20 articles up to July 2023, matching the search criteria with the keywords VD levels, CRS, and nasal polyps [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this review is to highlight the effect of VD levels on the pathogenesis and clinical manifestations of CRSwNP/sNP and clarify any therapeutic value of this hormone, in addition to current therapies for CRS. For this review, we managed to collect 20 articles up to July 2023, matching the search criteria with the keywords VD levels, CRS, and nasal polyps [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The other 116 studies were excluded as they related VD levels with other conditions (e.g., allergic rhinitis) and due to other reasons (e.g., written in languages other than English, literature reviews, meta-analyses, case reports, duplication). Although we identified two more eligible records through the manual research of the above-mentioned studies, 20 records were included in the current review [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Searching Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Other than rAOM, Abdel-Rahman et al [33] evaluated the role of vitamin-D levels in patients with Sino-nasal polypi and compared these levels to values of healthy individuals, and reported significant reduction among patients with nasal polypi or allergic rhinitis. They concluded that, vitamin-D is a cheap therapeutic agent which could be used as a prophylactic therapeutic option in reduction of inflammation (working directly by itself or through a synergistic agent besides traditional therapeutic option].…”
Section: Esposito and Leliimentioning
confidence: 99%